Financial Distress in Garment Company: During the Covid-19 Pandemic - Tyahya Whisnu Hendratni; Yudha Luthfie Ananta; Sekar Jati Ningrum (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Financial distress is characterized by a decline in the company's financial condition to the point of inability to meet its obligations. Financial distress is when a company faces financial difficulties that will lead to bankruptcy. Companies need to anticipate bankruptcy by measuring the level of financial distress using the Altman Z-Score method. This study aims to determine the results of financial distress predictions in the garment industry listed on the Indonesia Stock Exchange for 2018-2021 using the Z-Score model and to predict the financial distress conditions in the following year. This research uses a purposive sampling method by setting specific criteria to select samples, so six companies from 2018-2021 were taken as samples. Based on the data analysis, it can be concluded that there are five garment companies in the distress zone during the period 2018-2021 and 1 company in the grey zone in 2018 and 2019 but in 2020 and 2021 in the distress zone. The financial distress conditions for the next year in the garment products industry listed on the Indonesia Stock Exchange show that the company is in the distress zone.